KONSEP PEMIKIRAN ABDURRAHMAN WAHID TENTANG ISLAM KOSMOPOLITAN - Samsudin Samsudin; Siti Nurbaya (FiTUA: Jurnal Studi Islam, 2022)
This writing describes the fruit of Abdurahman Wahid's thoughts on Cosmopolitan Islam which emphasizes more on the basic essence of Islamic teachings, not just symbols and mere religious formalities. Cosmopolitan Islam is Gus Dur's genius thought in responding to actual issues that are directly related to issues of religion, culture, politics and development in the 1980-1990s. In cosmopolitan Islam Gus Dur invites the wider community to always hold fast to values universalism of religion, nationalism and upholding the attitude of openness to accept differences.